Neurodevelopmental outcomes of extremely preterm infants: theoretical and epidemiological perspectives to guide shared-care decision-making. Issue 1 (January 2022) - Fernandes, Michelle; Hanna, Sean; Sharma, Alok
Abstract: Although births below 28 completed weeks' of gestation contribute to less than 1% of all preterm births globally, the impact of extreme prematurity (EPT) on neurodevelopmental outcomes across the life-course is disproportionately large. Higher rates and increased severity of neurodevelopmental impairments (NDIs) are reported among extremely preterm infants (EPIs). Cognitive skills, motor skills (manifesting as cerebral palsy) and vision are most commonly affected, with effects pervasive throughout school, adolescence and early adulthood. In addition, poorer academic outcomes and higher rates of psychiatric morbidity are seen among EPTs. Consistent improvements in EPI survival in recent years has not been matched with improvements in neurodevelopmental outcomes, especially for those born at less than 25 gestational weeks. However, over the last 20 years, several national and cross-national cohort studies have helped advance our understanding of extreme prematurity's developmental and life-course consequences. Here we provide an overview of the key findings from 13 multi-centre cohorts measuring neurodevelopmental outcomes and discuss the theoretical and epidemiological perspectives of NDIs in the context of extreme prematurity to guide communication with families and shared care decision-making.